Activated Renal Dendritic Cells Cross Present Intrarenal Antigens After Ischemia-Reperfusion Injury. Issue 5 (May 2017) - Snelgrove, Sarah L.; Lo, Cecilia; Hall, Pam; Lo, Camden Y.; Alikhan, Maliha A.; Coates, P. Toby; Holdsworth, Stephen R.; Hickey, Michael J.; Kitching, A Richard
Abstract : Background: The healthy kidney contains an extensive population of renal mononuclear phagocytes (RMPs), with substantial phenotypic and functional diversity. However, how this diverse population is affected by ischemia-reperfusion injury (IRI), an obligate part of renal transplantation, is not yet well understood. The aim of this study was to characterize the phenotypic and functional alterations in RMPs induced by IRI. Methods: Renal mononuclear phagocytes were studied 24 and 72 hours after 30 minutes of renal ischemia or sham operation. Kidneys were digested and the phenotypes of renal leukocyte populations were analyzed via flow cytometry. Multiphoton microscopy was used to image renal dendritic cells (DCs) in vivo using CD11c reporter mice. The capacity of renal DCs to present antigen was examined by assessment of proliferation of ovalbumin-specific T cells in rat insulin promoter-membrane-bound ovalbumin transgenic mice after sham or IRI procedures. Results: Ischemia-reperfusion injury induced influx of monocytes, DCs, macrophages, and neutrophils into the kidney. Classification of RMP subpopulations based on CD11b/CD11c expression demonstrated that the RMPs that increased in response to IRI were predominantly newly recruited monocyte-derived inflammatory DCs. In vivo multiphoton imaging of CD11c-EYFP mice revealed that intrarenal DCs exhibited increased number and activity of dendrites in the postischemic period. Ischemia-reperfusion injury also promoted DC-dependent cross-presentation of renal antigens to CD8 + T cells in the draining lymph node. Conclusions: In response to renal IRI, RMP populations are skewed toward those derived from inflammatory monocyte precursors. In addition, renal DCs undergo functional activation, increasing their capacity to activate antigen-specific CD8 + T cells in renal draining lymph nodes. Abstract : Kidney ischemia-reperfusion injury results in accumulation of monocyte-derived inflammatory dendritic cells, renal dendritic cells become more active morphologically and cross-present renal antigens to CD8+ cells in draining lymph nodes. Supplemental digital content is available in the text.